2014
DOI: 10.9790/0837-19123746
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Subcontract Offering on the Performance of Manufacturing Micro and Small Enterprises in Kenya

Abstract: This study set out to investigate the influence of intensity of participation in subcontract offering on the performance of manufacturing micro and small enterprises (MSEs) in Kenya. The study used an exploratory research design targeting a population of 2450 MSEs from Kamukunji 'JuaKali' Association, Nairobi Kenya. A random sample of 180 firms returned 175 (97.2%) valid responses. Survey data was collected with a semistructured questionnaire through face-to-face interviews. A pilot test on 20 firms helped to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
0
5
0
2
Order By: Relevance
“…The financial indicators are: sales growth, growth in profits, changes in assets by gross value plant and machinery, return on assets to measure capital efficiency. The non-financial indicators are: growth in market share; product success; increase in number of employees and labour productivity (Gakure, Kimemia, & Waititu, 2014;Hu, Zheng, & Wang, 2011;Kongmanilaa & Takahashib, 2009;Marimuthu, Arokiasamy, & Ismail, 2009;Nwokocha & Madu, 2015;Ongonga & Abeka, 2011;Tuan & Yoshi, 2010). This was used by this paper to probe whether innovations of SMEs contributed to their performance in Nigeria.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…The financial indicators are: sales growth, growth in profits, changes in assets by gross value plant and machinery, return on assets to measure capital efficiency. The non-financial indicators are: growth in market share; product success; increase in number of employees and labour productivity (Gakure, Kimemia, & Waititu, 2014;Hu, Zheng, & Wang, 2011;Kongmanilaa & Takahashib, 2009;Marimuthu, Arokiasamy, & Ismail, 2009;Nwokocha & Madu, 2015;Ongonga & Abeka, 2011;Tuan & Yoshi, 2010). This was used by this paper to probe whether innovations of SMEs contributed to their performance in Nigeria.…”
Section: Conceptual Framework and Literature Reviewmentioning
confidence: 99%
“…Ini dikarenakan perusahaan yang lebih besar mampu menjadi sumber modal, memberi jaminan kualitas produk, akses pasar untuk penjualan, dan jangkauan distribusi yang lebih luas (Wattanapruttipaisan, 2002). Kemitraan subkontrak memiliki dampak positif untuk perkembangan UKM (Kumar & Subrahmanya, 2007;Gakure, Kimemia, & Waititu, 2014). Kemitraan subkontrak menyangkut hubungan pembayaran dan penawaran dimana UKM berkedudukan sebagai subkontraktor atau penyedia produk atau jasa bagi suatu kegiatan produksi (Kumar & Subrahmanya, 2007).…”
Section: Pendahuluanunclassified
“…Prinsipal memiliki toko pribadi atau sudah memiliki pasar tersendiri untuk memasarkan produk tersebut baik di dalam kota maupun luar kota Pekalongan. Kondisi ini sesuai dengan pendapat Gakure et al (2014), Kumar & Subrahmanya (2007), dan Wattanapruttipaisan (2002) yang menunjukkan bahwa kemitraan subkontrak memiliki dampak positif bagi perkembangan UKM karena terdapat suatu hubungan yang saling melengkapi antar industri yang terlibat terutama dalam hal modal, penyediaan bahan baku, dan pasar.…”
Section: Tabel 2 Jaringan Aktivitas Produksi Batik Kota Pekalonganunclassified
“…These empirical findings, however, did not state the influence or contributions of these constraints to the performance of manufacturing industries. Following the findings of Berry (1997), Yasuda (2005), Marsall, Mcivor, and Lamming (2007), and Gakure et al (2014)), which suggested that subcontracting has a positive impacts on firm's performance and the works of Hu et al (2011), which observed that there is no significant relationship between subcontracting and firm performance, it will be difficult to make an informed assessment on the influence of subcontracting constraints on firm performance. This work is thus oriented to investigate the influence of subcontracting constraints on the performance of manufacturing industries in Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…The financial indicators are: sales growth, growth in profits, changes in assets by gross value plant and machinery, return on assets to measure capital efficiency. The non-financial indicators were: growth in market share; product success; increase in number of employees and; labour productivity (Gakure, Kimemia, & Waititu, 2014;Hu, Zheng, & Wang, 2011;Kongmanilaa & Takahashib, 2009;Marimuthu, Arokiasamy, & Ismail, 2009;Ongonga & Abeka, 2011;Tuan and Yoshi, 2010).…”
Section: Introductionmentioning
confidence: 99%